2018
DOI: 10.18535/jmscr/v6i5.68
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Index Assessed from a Pulse Oximeter as a Predictor of Hypotension during Spinal Anaesthesia for Caesarean Section

Abstract: Background and Aims: Hypotension during spinal anaesthesia for caesarean section is a common and important problem with foetal and maternal implications. Perfusion Index (PI) observes from a pulse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…[ 16 ] also concluded a significant correlation between PI and the decrease in the systemic arterial pressure, but they had derived a baseline PI of 3.6 as their cutoff value with a sensitivity 80% and specificity of 60%. Varghese[ 17 ] conducted a similar study and concluded the same positive correlation result with an area under the curve of 0.911 and with the same baseline PI of 3.5 having a sensitivity of 86.6% and specificity of 93.33%. A more recent study by Mallawaarachchi et al .…”
Section: Discussionmentioning
confidence: 75%
“…[ 16 ] also concluded a significant correlation between PI and the decrease in the systemic arterial pressure, but they had derived a baseline PI of 3.6 as their cutoff value with a sensitivity 80% and specificity of 60%. Varghese[ 17 ] conducted a similar study and concluded the same positive correlation result with an area under the curve of 0.911 and with the same baseline PI of 3.5 having a sensitivity of 86.6% and specificity of 93.33%. A more recent study by Mallawaarachchi et al .…”
Section: Discussionmentioning
confidence: 75%
“…[ 5 ] Varghese RV found that the incidence of hypotension in group 1 (PI >3.5) was 86.67% whereas in group 2 (PI ≤3.5) was 6.67% which was highly significant (p < 0.05). [ 6 ] George et al . found that the incidence of hypotension was 66.7% among the study subjects and they concluded that the incidence and severity of hypotension was higher in parturients with baseline PI >3.6.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Clinical studies demonstrated that an increase in PI is an early indicator that spinal anesthesia has initiated peripheral vasodilation which typically occurs before the onset of anesthetic effect; however, the literature is limited. [ 5 6 ] Thus, PI can be used as a marker of peripheral perfusion and can be used to assess peripheral perfusion dynamics due to changes in peripheral vascular tone and to detect the likelihood of development of hypotension following spinal anesthesia. Hence, the present study was conducted to evaluate and correlate PI with incidence of hypotension following spinal anesthesia for caesarean section.…”
Section: Introductionmentioning
confidence: 99%
“…Dugappa et al found 3.85 as cut-off of baseline PI with sensitivity and specificity of 76% [9] . Varghese et al found 3.83 as a more appropriate cut-off value with a 86.67% sensitivity and 93.33% specificity, positive predictive value of 92.86% and negative predictive value of 87.5% [12] .…”
Section: Discussionmentioning
confidence: 99%